El loto en el estanque. Canon y diversidad en la India clásica. Ciudad de México: UNAM, PUEAA. ISBN: 978-607-30-5874-2 - Manzano, Paola Castillo (2023)
In this PUEAA's editorial novelty, mexican polymath on indian culture Óscar Figueroa writes ten essays that give a holistic understanding of inherent sociocultural elements to Sanskrit literary creation. Furthermore those essays, this book includes a section of key passages in classic works such as Mahābhārata and Rāmāyaṇa. It must be know that Sanskrit to Spanish translation of these passages was also in Figueroa's charge.